2015
DOI: 10.1016/j.ajps.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Improved dissolution and bioavailability of silymarin delivered by a solid dispersion prepared using supercritical fluids

Abstract: Available online xxxKeywords: Silymarin Solution-enhanced dispersion by supercritical fluids Solid dispersion Dissolution Bioavailability a b s t r a c tThe objective of this study was to improve the dissolution and bioavailability of silymarin (SM). Solid dispersions (SDs) were prepared using solution-enhanced dispersion by supercritical fluids (SEDS) and evaluated in vitro and in vivo, compared with pure SM powder.The particle sizes, stability, and contents of residual solvent of the prepared SM-SDs with SED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…In the literature, comparable findings to our results have been reported for Artemisia asiatica (Ryu et al, 1998), Cassia fistula (Bhakta et al, 2001), Cassia occidentalis (Yadav et al, 2010), Litchi chinensis (Bhoopat et al, 2011), and Sorbus pohuashanensis (Yin et al, 2019), among others. The serum rises in transaminases (GPT and GOT) and ALP, enzymes of cytoplasmic location, have been attributed to the damaged structural integrity of the liver (Ryu et al, 1998), allowing this enzyme to release into the blood stream after cell injury or death.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, comparable findings to our results have been reported for Artemisia asiatica (Ryu et al, 1998), Cassia fistula (Bhakta et al, 2001), Cassia occidentalis (Yadav et al, 2010), Litchi chinensis (Bhoopat et al, 2011), and Sorbus pohuashanensis (Yin et al, 2019), among others. The serum rises in transaminases (GPT and GOT) and ALP, enzymes of cytoplasmic location, have been attributed to the damaged structural integrity of the liver (Ryu et al, 1998), allowing this enzyme to release into the blood stream after cell injury or death.…”
Section: Discussionsupporting
confidence: 92%
“…However, the low bioavailability of SLM restricts its therapeutic efficacy [ 5 ]. It has been reported that the encapsulation of SLM in polymer nanoparticles, liposomes, micelles and solid lipid nanoparticles improves its solubility and bioavailibity [ 6 , 7 , 8 , 9 , 10 ]. Liposomes are used to deliver small lipophilic and hydrophilic agents, large proteins and nucleic acids.…”
Section: Introductionmentioning
confidence: 99%
“…In order to circumvent such a disadvantage, numerous methods for its synthesis have been proposed in order to increase the solubility and bioavailability of silibinin. This has included the implementation of solid lipid nanoparticles via encapsulation [ 20 ], incorporation in solid dispersion systems [ 21 ], and complexation with phospholipids [ 22 ]. A previous study by Zhang et al utilized stearic acid as a colloidal carrier for the encapsulation of silibinin.…”
Section: Introductionmentioning
confidence: 99%